Simulation of Automatic Rail Portal Closing Doors Using Regular Straight Movement Form - Sri Winar (Mulia International Journal in Science and Technical, 2019)
A train station is an essential tool, but the services provided to train passengers are still not optimal. At present, there are still some weaknesses, including the arrival and departure of trains that always rely on telephone communication with other station officials. Notification of train arrival will be conveyed by telephone by officers at the station beforehand to the destination station. When receiving an information on entry, the station clerk will close the railroad portal. The process can have a weakness, and if officer negligence occurs, it can cause an accident. Also, for train passengers who will board at the train station, there is no formal notification related to the arrival of the train. This is due to the absence of an automatic operating system at the railroad crossing portal. Because the manual system must use human power or operators to operate open and close railroad crossing portals. So the operator error and the failure of portal operations that can manually lead to the higher possibility of a train accident at the crossing entrance. The above problems can be overcome by implementing a portal closure system automatically. With an automated portal system, the portal will automatically close if there will be a train crossing the crossing. And the portal will automatically reopen if the passenger has passed the bridge. So it is expected that with this automatic portal closure system, traffic accidents due to not closing the portal when the train crosses the bridge can be avoided.